The Religion concept and the emergence - Asma Alalwani (Journal of Umm Al-Qura University for Shari'ah Sciences and Islamic Studies, 2022)
Praise be to Allah and prayers be upon the Messenger of Allah, and thereafter. The importance of this topic emerges in its handling of the ambiguities which contemporary atheistic thought is based upon. These ambiguities are exacerbated by today's media openness, which exposes correct and corrupt ideas under a variety of topics unrelated to religion, such as education, economy, history, and morals; as a result, the concept of religion and its origins are formulated in a way that contradicts the correct doctrine. It leads to a confusion between truth and falsehood, especially among Muslims who lack a sense of critical thought. The subject becomes worse when faith and intellectual immunity are weakened and unable to withstand confrontations. Therefore, confronting these attacks was one of the most important reasons for writing this research, to clarify the truth and reveal the falsehood. The research delved into it by explaining the concept of religion and the emergence of religiosity and its stimulants. One of the most prominent results is as follows: elucidation of flaws in Western scholars' hypotheses about the motivation for human religiosity, as their statements were based on assumptions. However, as the revelation indicates, religiosity is intrinsic. If this instinct is spared from conflicting exposures while positive reminders are present, it will be led to the truth. Similarly, if deviations occur, astray it goes, lead to religions of misguidance. As a result, we discover that religiosity is a universal phenomenon that exists among all people in all places and periods. The research also dealt with matters related to the beginning of religiosity. Posing the following questions: is religiosity the origin of humanity, then deviances occurred, or is the origin polytheism, then followed by monotheism? Furthermore, the corrupt and correct ways of inference are presented to demonstrate with evidence that monotheism is intrinsic in humans and polytheism is an external occurrence. As such, prophets were sent to return humanity to its original state.